2022
DOI: 10.9734/jpri/2022/v34i21a35835
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of Fracture Resistance of Teeth Obturated with a Novel Sealer: Chitra CPC with Endosequence BC Sealer, MTA Fillapex and AH Plus

Abstract: Background:  Bonding of sealer to root canal walls is likely to increase the integrity of the sealer-dentin interface during mechanical stresses, thus increasing resistance to fracture. Chitra-CPC sealer is an indigenously manufactured bioceramic material and has been used as bone graft and perforation repair material. When used as a sealer, it has good potential to reinforce the root strength in addition to excellent biocompatibility. Aim: To compare the fracture resistance of teeth obturated with novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…There were no previous studies that evaluated the effect of Endosequence BC HiFlow on root fracture resistance, but the results of this study agreed with Gervini et al, Varghese et al, and Yendrembam et al, where the resistance of roots to fracture was studied with the use of EndoSequence BC and AHP filler pastes. Studies concluded with results similar to this study, where there were no statistically significant differences [ 23 - 25 ].…”
Section: Discussionsupporting
confidence: 87%
“…There were no previous studies that evaluated the effect of Endosequence BC HiFlow on root fracture resistance, but the results of this study agreed with Gervini et al, Varghese et al, and Yendrembam et al, where the resistance of roots to fracture was studied with the use of EndoSequence BC and AHP filler pastes. Studies concluded with results similar to this study, where there were no statistically significant differences [ 23 - 25 ].…”
Section: Discussionsupporting
confidence: 87%